Alphakids: city and country - Feely, Jenny; Curtain, Michael (Eleanor Curtain Publishing Prahran, 2004)
"City and Country" is a delightful picture book that explores the contrasting experiences of life in urban and rural settings. Through vibrant illustrations and simple text, it showcases the hustle and bustle of the city$1 (Bfilled with tall buildings, busy streets, and diverse activities$1 (Bcompared to the tranquility of the countryside, featuring open fields, farms, and nature. The narrative encourages young readers to appreciate the unique qualities of both environments, celebrating the beauty and excitement each offers while fostering an understanding of different lifestyles and communities.s